2-(3-Cyano-4-{7-[1-(2-hydroxyethyl)-3,3-dimethylindolin-2-ylidene]hepta-1,3,5-trienyl}-5,5-dimethyl-2,5-dihydrofuran-2-ylidene)malononitrile - Gainsford, Graeme J. (International Union of Crystallography, 2011)
The title compound, C(29)H(28)N(4)O(2), excluding the hydroxyethyl and methyl groups, is slightly twisted from planarity so that the terminating indol-2-ylidene and furan-2-ylidene moiety planes subtend a dihedral angle of 6.27 (8)°. A small inwards fold in the polymethine atom chain is consistent with centrosymmetric dimer formation via O—H⋯N(cyano) hydrogen bonds. In the crystal, the molecules pack in layers approximately parallel to the (10[Image: see text]) plane via pairs of O—H⋯N and C—H⋯N(cyano) interactions.